Habitat Characteristics of Maleo (Macrocephalon maleo) Nesting Sites in Bukit Jaya Village, Banggai Regency, Indonesia - Nuraini Nuraini; Sutrisnawati Sutrisnawati; Manap Trianto; Fatmah Dhafir; Rafiqa Rafiqa; Masrianih Masrianih (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The Maleo (Macrocephalon maleo) is an endemic bird species found in Central Sulawesi, Indonesia. This species belongs to the order Galliformes and is distinguished by a prominent black, hard casque on its head, an orange beak, predominantly black plumage, and yellowish facial skin. The Maleo exhibits a unique reproductive strategy, as it does not incubate its eggs directly. Instead, it buries them in loose sandy soil that is naturally heated by geothermal activity. According to the 2021 assessment by the International Union for Conservation of Nature (IUCN), the Maleo is classified as Critically Endangered under criteria A2cd+4cd (Version 3.1) of the IUCN Red List. This study aimed to describe the characteristics of Maleo nesting habitats in Bukit Jaya Village, Banggai Regency, in order to support the conservation of suitable in situ breeding and nesting environments. The study employed a descriptive qualitative approach, focusing on direct field observations and literature review. Sampling stations were determined using an exploratory survey method, in which sites were purposively selected based on habitat characteristics to observe Maleo nesting conditions and the surrounding vegetation. Data collected included nesting-hole depth and width, temperatures inside and outside the nesting holes, sand surface temperature, and humidity. Measurements were conducted three times daily at 08:00, 13:00, and 17:00. The results showed that: (1) nesting-hole depth ranged from 43 to 46 cm, with an average of 44.4 cm; (2) nesting-hole width ranged from 47 to 53 cm, with an average of 50 cm; (3) between 08:00 and 17:00, the average temperature inside the nesting holes was 31°C, the average temperature outside the holes was 35.74°C, the average sand surface temperature was 36.2°C, and the average relative humidity was 72.62%; and (4) the nesting habitat in Bukit Jaya Village was characterized by diverse vegetation growth forms, including trees, shrubs, herbs, and climbing plants (lianas). A total of 16 plant species belonging to 12 families were identified within the nesting habitat. The protection of nesting habitats should be continuously strengthened to help prevent the extinction of this valuable and iconic bird species.